2014
DOI: 10.1016/j.jaci.2014.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Airway surface mycosis in chronic TH2-associated airway disease

Abstract: Background Environmental fungi have been linked to T helper type 2 (Th2) cell-related airway inflammation and the Th2-associated chronic airway diseases asthma, chronic rhinosinusitis with nasal polyps (CRSwNP) and allergic fungal rhinosinusitis (AFRS), but whether these organisms participate directly or indirectly in disease pathology remains unknown. Objective To determine the frequency of fungus isolation and fungus-specific immunity in Th2-associated and non-associated airway disease patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 35 publications
1
80
0
1
Order By: Relevance
“…540,541 Some evidence suggests that IL-33 may play a role as well, but these studies have yet to demonstrate increased expression of this cytokine at the protein level in NP tissue. 374,[542][543][544] In regard to IL-25, evidence in CRS is scant. As mentioned earlier in this section EC chemokines also play a major role in the attraction and activation of innate effector cells including eosinophils, mast cells, neutrophils, macrophages, and likely ILCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…540,541 Some evidence suggests that IL-33 may play a role as well, but these studies have yet to demonstrate increased expression of this cytokine at the protein level in NP tissue. 374,[542][543][544] In regard to IL-25, evidence in CRS is scant. As mentioned earlier in this section EC chemokines also play a major role in the attraction and activation of innate effector cells including eosinophils, mast cells, neutrophils, macrophages, and likely ILCs.…”
Section: Discussionmentioning
confidence: 99%
“…372,373 The presence of fungi seen in the sinuses of CRS patients may be explained by delayed MCC, and may therefore be a downstream effect of inflammation rather than a cause. Although some studies have shown increased fungal loads in some CRS patients compared to controls, 374,375 others have revealed no difference in either prevalence rates of fungus or number of different fungi recovered. 361,376 Numerous studies, including multiple RCTs, have examined the role of antifungal treatment in CRS and none have shown a clinically meaningful improvement.…”
Section: S55mentioning
confidence: 97%
“…Porter et al recently reported that environmental fungi directly contribute to the pathogenesis of chronic Th2-related airway diseases (5). Recently, we have described the inhibition of IFN-β signaling through JAK-STAT1 by Aspergillus fumigatus (AF) in bronchial epithelium, resulting in reduced induction of CXCL10, also known as IFN-γ induced protein 10 (IP-10), a chemokine that attracts Th1 cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may account for the presence of Alp 1 (and probably other protease allergens) in the bronchial submucosa in people with asthma but not in healthy people. Recent clinical studies have demonstrated higher rates of surface airway mycosis in subjects with asthma (74%) than in controls (16%), and fungal-induced T H 2 immunity is restricted to asthma 40 . Lungs of asthmatic subjects with Af sensitivity (positive skin prick test) may be more susceptible to germination of Af spores and have a higher burden of Af recoverable from sputum 41 .…”
Section: Discussionmentioning
confidence: 99%